p62/Sqstm1 rescue in muscle retards the progression of steatohepatitis in p62/Sqstm1-null mice fed a high-fat diet - Miura, Ikuru; Okada, Kosuke; Ishii, Akiko; Warabi, Eiji; Watahiki, Takahisa; To, Keii; Shimano, Hitoshi; Ariizumi, Shunichi; Shoda, Junichi (Frontiers in Physiology, 2022)
Introduction: Obesity is a risk factor for many diseases because it leads to a reduction in skeletal muscle mass and promotes insulin resistance. p62/Sqstm1-knockout mice are a model of metabolic syndrome; show obesity, insulin resistance, and non-alcoholic fatty liver (NAFL); and develop non-alcoholic steatohepatitis (NASH) in response to the feeding of a high-fat diet (HFD). These phenotypes suggest that muscle p62 may prevent obesity-induced muscle dysfunction. In the present study, we aimed to determine the effects of muscle p62 on skeletal muscle mass, muscle strength, insulin resistance, and NASH pathology. Methods: We generated muscle-specific p62 gene rescue mice (p62-mRes), which express p62 only in muscle and were derived from p62-knock out mice (p62KIKI) using the cre/loxp system. p62KIKI and p62-mRes mice were fed an HFD for 20 weeks and their phenotypes were compared. Results: HFD-feeding caused severe obesity in both p62KIKI and p62-mRes mice, but there was no effect of muscle p62 on body mass. Limb skeletal muscle mass, grip strength, and the cross-sectional area of muscle fibers were higher in p62-mRes mice than in p62KIKI. The glucose tolerance and insulin sensitivity of the p62-mRes mice were also superior. The protein expression of mechanistic target of rapamycin, which promotes muscle protein synthesis, and GLUT4, a glucose transporter in skeletal muscle, were higher in the p62-mRes mice. p62KIKI mice developed severe NASH when fed an HFD, but the progression of NASH was retarded by p62 gene rescue in muscle, and the expression of Tgf-β1, which encodes a factor that promotes hepatic fibrosis, was reduced. Conclusion: Rescue of muscle-specific p62 in the whole-body p62 knock-out mice ameliorates the insulin resistance and retards the progression of NASH caused by systemic p62 ablation.